Failure Analysis on Leaked Tube of Furnace Boiler - Sukandar; Triwibowo; Aswandi (Program Studi Teknik Mesin Universitas Pamulang, 2024)
Furnace in oil companies is functioned to heat raw oil in process to produce various fuels, and outlet gas from the furnace is used for heating water in Furnace Boiler. Failure took place on tubes of Furnace Boiler. The purpose of this failure analysis is to find the root cause of failure. Methods conducted in this failure analysis are through examination and testing of fractography, metallography, chemical composition, hardness, and bulging measurement. Examination on the fracture surface by fractographic method revealed leakage due to excessive bulging and existence of excessive deposit/scale. Condition of bulging gave indication of long-term overheating due to excessive deposit/scale. Examination by metallographic method revealed that microstructure of ferrite and pearlite having grain growth due to exposed by local heating. However, result of chemical composition examination and hardness test showed that material of the furnace tubes were in accordance with ASTM A-192. Bulging measurement gave indication of excessive bulging up to 15% for the leaked tube. Therefore, failure of leaked tube of Furnace Boiler was caused by long-term overheating due to excessive deposit/scale which were formed in the location of bulging.